2015
DOI: 10.1007/s12205-015-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the factors that influence drivers’ willingness to use the parking guidance information

Abstract: Parking Guidance and Information (PGI) System becomes highly favorable for reducing circulating traffic and making efficient use of existing parking facilities. This paper is to examine the factors influence drivers' willingness to use PGI. Factor analysis and the Structure Equation Model (SEM) were used to identify the latent attitudinal factors and the sensitivity of the factors was judged by Bayesian network. The heterogeneity of the factors was explored based on driver's gender, age, driving years, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They found that when there is no music while driving, women drive at a more appropriate speed than men, while in the presence of music women have a greater chance of committing either a minor or a major speed violation, with music acting as a factor of distraction. Ji et al [24] used different tools including factor analysis, structural equation modeling (SEM), and BNs to evaluate factors influencing the willingness to use parking guidance and information (PGI) systems and the different perceptions of men and women. They found that female drivers are more likely to use PGI to get help when they realized that it is hard to find a parking space, with a level of willingness of 63.6% compared with 10.9% for male drivers.…”
Section: Bayesian Network Applied To Autonomous Vehicles-driver Inter...mentioning
confidence: 99%
“…They found that when there is no music while driving, women drive at a more appropriate speed than men, while in the presence of music women have a greater chance of committing either a minor or a major speed violation, with music acting as a factor of distraction. Ji et al [24] used different tools including factor analysis, structural equation modeling (SEM), and BNs to evaluate factors influencing the willingness to use parking guidance and information (PGI) systems and the different perceptions of men and women. They found that female drivers are more likely to use PGI to get help when they realized that it is hard to find a parking space, with a level of willingness of 63.6% compared with 10.9% for male drivers.…”
Section: Bayesian Network Applied To Autonomous Vehicles-driver Inter...mentioning
confidence: 99%